Pilot survey studies on tourism capacity building in Sarawak 2011 / Ranee Atlas … [et al.]. - Atlas, Ranee; Putit, Nuraini; Geikie, Gracie V. (2012)
The study on Capacity Building Pilot Survey of the Sarawak Tourism Industry is held in conjunction with the Sarawak Tourism Lab: Revisiting Sarawak Tourism Master Plan, from 24 to 25 February and 28 February till 2 March, 2011. During the Capacity Building Lab, the team had syndicated various agencies, to identify and to create new policies for training areas, research questionnaire, comparing rating and etc.